Whether stock market provides high returns: evidence from skewness of individual stocks in China. Issue 2 (7th September 2020) - Ma, Tianning; Li, Shuo; Feng, Xu
Abstract : Purpose: This paper studies whether individual stocks provide higher returns than government bond in the Chinese market. Design/methodology/approach: The authors compare individual stock returns and government bond returns in the Chinese market. Findings: The authors find that more than half of individual stocks underperform government bonds over the same period in China, which highlights the important role of positive skewness in the distribution of individual stock returns. The high return of a few stocks is the reason why the stock market return is higher than that of government bond in China. Originality/value: The results of this paper emphasize that portfolio diversification plays an important role in the Chinese market.